Mapping Trends in Doctoral Dissertations in English Language Education: A Systematic Analysis of Doctoral Research at Universitas Negeri Makassar - Dollah, Syarifuddin; Sakkir, Geminastiti (ELT Worldwide: Journal of English Language Teaching, 2025)
This study aims to systematically map the research trends in doctoral dissertations produced by Ph.D., candidates in the English Language Education Program at Universitas Negeri Makassar over the past three years (2021–2023). The objectives are threefold: (1) to describe the topics explored in doctoral dissertations, (2) to analyze the research approaches and methodologies employed by doctoral students, and (3) to identify research gaps that require further exploration to enrich the field of English Language Education. Employing a content analysis framework, 63 dissertations archived between 2021 and 2023 were systematically reviewed. The findings indicate a clear thematic shift from literacy- and culture-based studies (2021) toward the integration of digital technologies and advanced pedagogical innovations (2022), culminating in the use of artificial intelligence, hybrid learning, dialogic feedback, and 21st-century skills frameworks (2023). From a methodological perspective, the research trajectory evolved from qualitative ethnographic inquiries in 2021, toward mixed methods and research and development (R&D) designs in 2022 and 2023. Despite this progress, research gaps remain in three major areas: (1) language assessment and test validation, (2) longitudinal studies capturing long-term effects of learning innovations, and (3) equity and inclusion in EFL contexts such as remote, marginalized, and special needs learners. The study contributes to theoretical enrichment by extending the literature on doctoral-level research mapping in ELT, and offers practical and policy implications for doctoral candidates, supervisors, and program administrators.